Retrospective multicenter evaluation of patients diagnosed with mucosal melanoma: a study of Anatolian Society of Medical Oncology - (:unkn) unknown (SAGE PUBLICATIONS LTD, 2016)
Mucosal melanoma (MM) is a rare type of cancer that differs significantly from cutaneous melanoma. In this study, we aimed to evaluate clinical and demographical characteristics, prognoses and factors influencing survival, treatment alternatives, and features of different subtypes of the patients. The patients were followed up with and treated in different centers due to their diagnoses of MM. We retrospectively analyzed data of 107 patients who were diagnosed with MM in 14 different institutions in Turkey. The mean age of the patients was 64.5 years. Of the patients, 47 % were female and 53 % were male. The median overall survival (OS) was 17 months, and the mean follow-up duration was 27 months. The 2-year survival rate was 42 %, and the 5-year survival rate was 23 %. The best survival rate appeared in those patients with MM in the head-neck region (median survival rate was 27 months, P = 0.034). The most common anatomical site was the head-neck region. In a univariate analysis, variables including age aeyen65 years, the anatomical site of the primary lesion other than head and neck region, the metastatic stage of the disease, high levels of lactate dehydrogenase (LDH), and an Eastern Cooperative Oncology Group Performance Status (ECOG PS) of aeyen1 were found to be associated with poor survival (P < 0.05). However, in a multivariate analysis, only advanced stage disease (HR = 2.70; 95 % CI, 1.64-4.45; P = 0.000) and high LDH levels (HR = 2.31; 95 % CI, 1.40-3.80; P = 0.001) were determined to be adverse prognostic variables. Primary MM presents a more aggressive behavior and offers a poorer prognosis compared to cutaneous melanoma. Because the disease is rarely seen, is heterogeneous, and lacks randomized studies, issues concerning optimal treatment approaches and management and clinical characteristics of the disease have not been clarified yet.
Keywords: Mucosal melanoma; Head and neck; Anorectal; Genitourinary; MALIGNANT-MELANOMA; BRAF MUTATIONS; NONCUTANEOUS MELANOMA; HEAD; NECK; THERAPY; RADIOTHERAPY; VULVA